Faktor Komunikasi Dalam Organisasi - Ida Apriani; Raja Doli Siregar; Dedi Sahputra (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2021)
communication that creates a positive work climate in an organization in order to achieve organizational goals. The research methodology used is descriptive qualitative, while data collection is done through observation and structured interviews as well as other data in the form of related supporting documents. The results showed that communication greatly affects the work environment. In general, this work environment includes the relationship between employees, work relations between superiors and subordinates, between leaders and all employees, coordination between sections to the smallest unit in the organization's members. This communication greatly affects the working relationship or coordination between members of the organization. Poor communication directly affects work relations among members of the organization. A bad working relationship affects the performance of organizational members which in turn affects the productivity of the organization.